The awareness of knowledge, attitudes and practices on food hygiene among food handlers in school canteen in Dungun, Terengganu / Nur Bazilah Mohd Adam & Nor Fadhilah Mohamed - Mohd Adam, Nur Bazilah; Mohamed, Nor Fadhilah (2017)
The aim of this study is to determine the awareness of knowledge, attitudes, and practices on food hygiene among food handlers in the school canteen in Dungun, Terengganu. Only 64 of food handlers from school canteen were involved in this study. The statistics were gathered from the food handlers through the methods of questionnaire. Besides that, this research using the frequency descriptive analysis to analyse the data. Mostly the respondents were answered strongly agree to the statements in the both Section, which were Section B for the knowledge and Section C for the attitudes about food hygiene. Furthermore, the majority of the respondents were responded often to the statements in the Section D about the practices on food hygiene among food handlers. Besides that, some of the food handlers were given their suggestions to support the research objectives in the Section E. Besides that, the time constraint also occurred during to finish this research. For the future researcher, we also recommend for using the method of qualitative research like using interview, observation and focus group discussion can be used to support and make the comparison result of this study. As a conclusion, the food handlers must aware about the knowledge, attitudes and practices on food hygiene among school canteen to avoid from foodbome illness.